Adoption of hip hop fashion by selected dance groups in the Philippines - Pineda, Raphaela Martina C. (UP College of Home Economics, 2012)
From its origins as an African-American youth subculture in the ghettos of New York City, Hip Hop now refers to popular movements in music, art, and dance. Once considered the voice of a generation that longed to be seen and heard, Hip Hop has grown into a culture with a specific vernacular and its own mode of dress. Hip Hop Fashion currently runs in the mainstream, where it has branched out into different genres, each of which is associated with particular clothing styles. Hip Hop Fashion has been gaining popularity in the Philippines, but there is not much literature available on this phenomenon. It is in this light that the research was conducted. This study describes how Hip Hop Fashion was adopted by selected groups in the Philippine dance community. With the use of purposive sampling, data was gathered through interviews conducted wit three self-identified propagators of Bboying, Locking and Krump in the Philippines. Insights on the spread of Hip Hop fashion were also sought from nine more dancers currently involved in the cultural practices of each genre. Using a combination of Diffusion and Fashion Movement theories, the interviews were then profiled and analyzed for how Hip Hop fashion evolved through the clothing styles worn by the dancers. Responses found in the interviews with these individuals showed which aesthetic and functional qualities of clothing worn for Bboying, Locking, and Krumping were utilized for both training snd performances. As the preferred styles were adopted for their compatibility, character, and ease of use, they tricked further into the Philippine dance community, where they were accepted and adopted as Hip Hop Fashion.